The Image of Spanish Women in Press Photography during the Civil War. Content Analysis Applied to the Main Portuguese Newspapers. - García Castillo, Noelia (Historia y Comunicación Social, 2014)
The Spanish Civil War entailed an alteration in gender role assignment and propaganda activities. The conflict attracted the attention of numerous countries, especially that of Portugal because of its own interests. The Portuguese Press earmarked considerable funds to cover the warfare, but such coverage was biased in favour of the Nationalist faction. By means of a thorough content analysis, this paper discusses the stereotypes and models of Spanish women present in Portuguese photojournalism during the Spanish Civil War.
Keywords: Spanish Civil War; Woman; Stereotypes; Models; Portuguese Photojournalism; Propaganda.